2004
DOI: 10.1038/nsmb878
|View full text |Cite
|
Sign up to set email alerts
|

Unique binding interactions among Ubc9, SUMO and RanBP2 reveal a mechanism for SUMO paralog selection

Abstract: The conjugation of small ubiquitin-like modifiers SUMO-1, SUMO-2 and SUMO-3 onto target proteins requires the concerted action of the specific E1-activating enzyme SAE1/SAE2, the E2-conjugating enzyme Ubc9, and an E3-like SUMO ligase. NMR chemical shift perturbation was used to identify the surface of Ubc9 that interacts with the SUMO ligase RanBP2. Unlike known ubiquitin E2-E3 interactions, RanBP2 binds to the beta-sheet of Ubc9. Mutational disruption of Ubc9-RanBP2 binding affected SUMO-2 but not SUMO-1 conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
141
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 30 publications
5
141
0
Order By: Relevance
“…The SIM in the TAD is involved in fine-tuning the sumoylation of c-Myb in the EVES domain, such that, mutating the SIM reduces the sumoylation of c-Myb slightly (Figure 4a). Such interdependency has been shown for other SUMO targets, and reflects the fact that noncovalent binding of SUMO is an important mechanistic step in the conjugation reaction, orientating the SUMO moiety for optimal transfer (Reverter and Lima, 2005;Tatham et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The SIM in the TAD is involved in fine-tuning the sumoylation of c-Myb in the EVES domain, such that, mutating the SIM reduces the sumoylation of c-Myb slightly (Figure 4a). Such interdependency has been shown for other SUMO targets, and reflects the fact that noncovalent binding of SUMO is an important mechanistic step in the conjugation reaction, orientating the SUMO moiety for optimal transfer (Reverter and Lima, 2005;Tatham et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…Thus, we expressed increasing amounts of nonconjugatable SUMO1 and -2 (mono-Gly in C terminus) in the presence of our c-Myb mutants. We expected the nonconjugatable SUMO to interfere mainly with SUMO binding, but also indirectly with conjugation, as the conjugation process is dependent on SUMO interactions (Reverter and Lima, 2005;Tatham et al, 2005). As can be seen in Figure 6a, co-expression of SUMO1-1G in the presence of wild-type c-Myb led to an increase in transactivation, whereas no significant change in activity was observed for c-Myb ANAA 2KR.…”
Section: Sumo Binding and The Transforming Ability Of C-mybmentioning
confidence: 93%
“…Three SUMO E3s have been identified so far: the mammalian protein inhibitors of activated STAT (PIAS; Sachdev et al, 2001), the nucleoporin RanBP2 (Azuma and Dasso, 2002;Pichler et al, 2002), and the polycomb group protein PC2 (Kagey et al, 2003). Recent structural data provide novel insights into the mechanism used by E3s to enhance SUMO conjugation (Duda and Schulman, 2005;Reverter and Lima, 2005;Tatham et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Three SUMO E3s have been identified so far: the mammalian protein inhibitors of activated STAT (PIAS; Sachdev et al, 2001), the nucleoporin RanBP2 (Azuma and Dasso, 2002;Pichler et al, 2002), and the polycomb group protein PC2 (Kagey et al, 2003). Recent structural data provide novel insights into the mechanism used by E3s to enhance SUMO conjugation (Duda and Schulman, 2005;Reverter and Lima, 2005;Tatham et al, 2005).Removal of SUMO from proteins is carried out by specific cysteine proteases that have both hydrolase and isopeptidase activity Hochstrasser, 1999, 2000). Most enzymes involved in the SUMO pathway are localized in the nucleus, and it is therefore believed that sumoylation is predominantly a nuclear process (Rodriguez et al, 2001;Zhang et al, 2002;Seeler and Dejean, 2003).…”
mentioning
confidence: 99%
“…The stable interactions observed between RanGAP1 and E2; E3, SUMO and E2; and the covalent interaction between RanGAP1-SUMO suggested that our structure represented a trapped product complex. To test this, conjugation assays using RanGAP1 under multiple turnover conditions with and without Nup358/RanBP2 IR1* showed, in contrast to other substrates 12,18,19 , that IR1* inhibited SUMO conjugation. Importantly, SUMO-RanGAP1 accumulated to near stochiometric ratios of product, E2, and E3 ( Figure 4a).…”
mentioning
confidence: 99%